Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/aac.49.5.1739-1744.2005
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Genotype Interpretation of Resistance to Didanosine

Abstract: We analyzed the didanosine (ddI) arm of the randomized, placebo-controlled Jaguar trial in order to define a genotypic score for ddI associated with virologic response. In this arm, 111 patients experiencing virologic failure received ddI in addition to their current combination therapy for 4 weeks. The impact of mutations in the reverse transcriptase gene on the virologic response to ddI was studied in univariate analysis. Genotypic score was constructed using step-by-step analyses first including only mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
3
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 26 publications
3
43
3
1
Order By: Relevance
“…Subsequent studies have shown that the L210W mutation commonly occurs together with M41L and T215Y and contributes significantly to ZDV resistance (14,37). Moreover, didanosine and tenofovir are significantly less active against viruses that carry the 41L/210W/215Y combination (27,30). Our results provide additional insights that help explain the ordered appearance of ZDV resistance mutations.…”
Section: Vol 80 2006 Fitness Of Zidovudine-resistant Hiv-1 7023mentioning
confidence: 68%
See 1 more Smart Citation
“…Subsequent studies have shown that the L210W mutation commonly occurs together with M41L and T215Y and contributes significantly to ZDV resistance (14,37). Moreover, didanosine and tenofovir are significantly less active against viruses that carry the 41L/210W/215Y combination (27,30). Our results provide additional insights that help explain the ordered appearance of ZDV resistance mutations.…”
Section: Vol 80 2006 Fitness Of Zidovudine-resistant Hiv-1 7023mentioning
confidence: 68%
“…Mutations that occur together with T215Y (including M41L, L210W, and sometimes D67N) constitute the TAM-1 cluster; mutations that occur together with K70R (including D67N, T215F, and K219Q) constitute the TAM-2 cluster (10,26,36). The division of TAMs into two distinct clusters has important clinical significance: ZDV-resistant viruses carrying TAM-1 mutations usually are cross-resistant to didanosine and tenofovir, whereas viruses carrying TAM-2 mutations usually remain susceptible to those drugs (27,30). The T215Y mutation may be found by itself or in combination with M41L and L210W, but T215F rarely occurs alone or with the M41L and L210W mutations.…”
mentioning
confidence: 99%
“…The V82A mutation is known to emerge in subtype B HIV-1 following LPV therapy and to modestly decrease the level of binding between PIs and PR because of changes to the enzyme active-site cavity (17,22,23). Our results show that V82A results in a modest increase in the LPV fold resistance (Table 1) at great expense to viral replication capacity (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…This provides objective information for the guidance of drug selection based on genotypes, in particular for treatment-experienced patients (11,14,23). Here, we have identified a list of protease mutations that impair the virological response to boosted FPV in PI-experienced patients using stepwise methodologies as previously proposed (6,14,15,23). We described the mutations associated with FPV/r virological response at week 12 based on virological data from a pooled analysis of FPV/r 700/100 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…The removing procedure began with all k mutations retained from the univariate analysis. The nonparametric Jonckheere-Terpstra (JT) test for ordered alternatives that allows testing of a specific a priori sequence was used (6,10,15). From the initial set of k mutations, the first step was to remove one mutation.…”
Section: Methodsmentioning
confidence: 99%